Global Entry Model for Indian IT Industry: Theoretical and Empirical Approach - Naik, Subhash S.; Reddy, Y. V. (Prabandhan: Indian Journal of Management, 2010)
Indian IT industry had a very late start when compared to US or Europe. Yet in the last decade, Indian IT firms have emerged as a global powerhouse in computer software development. Indian firms have transformed from a modest coding and body shopping operation to become a global competitor in a leading edge sector. Indian IT consulting companies are now competing globally with the established industry giants. One of the most important characteristics of globalization is the opening of the national markets to foreign firms, something that has led to intensified competition in these markets (James Leontiades, 1986). Firms all over the globe realize that they cannot expect their sales and profits to grow at satisfactory rates unless they implement appropriate business strategies to sustain and possibly improve the competitiveness of their products in the international markets.